Silicon carbide defects and luminescence centers in current heated 6H-SiC - Lee, S.W.; Vlaskina, S.I.; Vlaskin, V.I.; Zaharchenko, I.V.; Gubanov, V.A.; Mishinova, G.N.; Svechnikov, G.S.; Rodionov, V.E.; Podlasov, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
At room temperature yellow photoluminescence with a broad peak of 2.13 eV
is a well-known feature of boron-doped 6H-SiC. Usually yellow luminescence is
regarded as recombination involving both the boron-related deep acceptor and donor
level. But the nature of the deep level has not been clearly understood yet. We annealed
6H-SiC substrates by current in vacuum without boron injection at the temperature of
1350 and 1500 ºC. We received red and yellow luminescence in PL spectrum for the
heated 6H-SiC. The luminescence was regarded as donor-acceptor pair recombination
involving the deep aluminum acceptor related to the adjacent carbon vacancies and
nitrogen donor or the formation of quantum well like regions of 3C-SiC in 6H-SiC
matrix.